PENERAPAN EVIDENCE BASED NURSING DENGAN INTERVENSI SLOW DEEP BREATHING UNTUK MENURUNKAN NYERI PADA PASIEN ANAK POST OPERASI DI RUANG PERAWATAN ADE IRMASURYANI 1 RSPAD GATOT SOEBROTO - Afdila (2023)
Pain is one of the vital signs that is the focus of attention in providing nursing care at the hospital. Pain management is divided into pharmacological and non-pharmacological therapy. Good pain management can improve the pain response experienced by clients. Nurses play a very important role in pain management. One of the therapies that can be applied by nurses in pain management is slow deep breathing. Slow deep breathing therapy is a non-pharmacological treatment in the form of relaxation therapy that helps reduce pain by breathing slowly, deeply and regularly. The purpose of this study was to analyze the application of slow deep breathing interventions to reduce pain intensity in postoperative children. The respondents involved in the study were two school-age children, including managed clients and resumes who were given the intervention for three days, carried out twice a day for 15-20 minutes. Measurement of pain scale using the Wong Baker Faces Pain Scale. The results of the assessment showed that there was a decrease in the pain scale in clients, both those who were managed and continued with the results of the third day, namely pain scale 1.